Evolutionary emergence of collective intelligence in large groups of students - Orejudo, Santos; Cano-Escoriaza, Jacobo; Cebollero-Salinas, Ana Belén; Bautista, Pablo; Clemente-Gallardo, Jesús; Rivero, Alejandro; Rivero, Pilar; Tarancón, Alfonso (Frontiers in Psychology, 2022)
The emergence of collective intelligence has been studied in much greater detail in small groups than in larger ones. Nevertheless, in groups of several hundreds or thousands of members, it is well known that the social environment exerts a considerable influence on individual behavior. A few recent papers have dealt with some aspects of large group situations, but have not provided an in-depth analysis of the role of interactions among the members of a group in the creation of ideas, as well as the group’s overall performance. In this study, we report an experiment where a large set of individuals, i.e., 789 high-school students, cooperated online in real time to solve two different exams on a specifically designed platform (Thinkhub). Our goal in this paper is to describe the specific mechanisms of idea creation we were able to observe, and to measure the group’s performance as a whole. When we deal with communication networks featuring a large number of interacting entities, it seems natural to model the set as a complex system by resorting to the tools of statistical mechanics. Our experiment shows how an interaction in small groups that increase in size over several phases, leading to a final phase where the students are confronted with the most popular answers of the previous phases, is capable of producing high-quality answers to all exam questions, whereby the last phase plays a crucial role. Our experiment likewise shows that a group’s performance in such a task progresses in a linear manner in parallel with the size of the group. Finally, we show that the controlled interaction and dynamics foreseen in the system can reduce the spread of “fake news” within the group.